2015
DOI: 10.1097/aud.0000000000000145
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Auditory Spectral Resolution on Listening Effort Revealed by Pupil Dilation

Abstract: Objectives This study measured the impact of auditory spectral resolution on listening effort. Systematic degradation in spectral resolution was hypothesized to elicit corresponding systematic increases in pupil dilation, consistent with the notion of pupil dilation as a marker of cognitive load. Design Spectral resolution of sentences was varied with 2 different vocoders: (1) a noise channel vocoder with a variable number of spectral channels; and (2) a vocoder designed to simulate front-end processing of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
322
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(366 citation statements)
references
References 83 publications
41
322
2
1
Order By: Relevance
“…Kramer et al 2016, this issue, 126S-135S). Research on cognitive processing load during listening using pupillometry has shown that the pupil response during listening is sensitive to speech intelligibility (Zekveld et al 2010), type of background noise (Koelewijn et al 2012), syntactic complexity (Piquado et al 2010), auditory stimulus characteristics , degraded spectral resolution (Winn et al 2015), cognitive abilities (Zekveld et al 2011), and divided (versus focused) attention (Koelewijn et al 2014). Cardiac Responses • Two cardiac measures that may be related to listening effort are heart-rate variability (HRV) and the PEP.…”
Section: Physiological Measuresmentioning
confidence: 99%
“…Kramer et al 2016, this issue, 126S-135S). Research on cognitive processing load during listening using pupillometry has shown that the pupil response during listening is sensitive to speech intelligibility (Zekveld et al 2010), type of background noise (Koelewijn et al 2012), syntactic complexity (Piquado et al 2010), auditory stimulus characteristics , degraded spectral resolution (Winn et al 2015), cognitive abilities (Zekveld et al 2011), and divided (versus focused) attention (Koelewijn et al 2014). Cardiac Responses • Two cardiac measures that may be related to listening effort are heart-rate variability (HRV) and the PEP.…”
Section: Physiological Measuresmentioning
confidence: 99%
“…This overall smaller increase in pupil dilation can be explained by the fact that these curves are normalized to a baseline of 200 ms preceding the presentation of each critical item per trial, participant and condition. Listening to degraded speech is by itself more effortful than listening to natural speech (e.g., Winn et al 2015), and therefore there is a difference in the baseline between DS and NS. These differences in the baseline can be explained by the difference in processing degraded versus natural speech, and are independent of the effects of semantic integration on lexical competition.…”
Section: Pupil Dilationmentioning
confidence: 99%
“…The findings of the present study reinforce the need for new tools or evaluation metrics in capturing benefits or treatment effectiveness beyond the traditional measure of percentage correct for speech intelligibility. Recent studies have shown a reduction in listening effort (measured by the reaction time to the secondary task or by the change of pupil size) as the quality of the auditory signal improved beyond the asymptotic performance in a recognition task (e.g., Sarampalis et al, 2009;Pals et al, 2013;Winn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%